2012
DOI: 10.1016/j.jcot.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical investigation into the torsional failure of immature long bone

Abstract: a b s t r a c tApproximately 50% of infant and toddler long bone fractures are attributed to nonaccidental trauma; however, differentiating from benign mechanisms is subjective, due to an absence of evidence-based diagnostic tools. Previous studies investigated small ranges of rotational velocities in animal long bone models, although did not report the variation in the spiral fracture angle. This study considered the fracture angle as a potential clinical measure, correlating this data with a wider range of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
4
9
0
Order By: Relevance
“…The predicted maximum principal strain under torsion was located at the narrowest cross-sectional area of the diaphysis, namely the mid-shaft. This is in agreement with previous experimental studies of long bones under pure torsional loads (Kress et al 1995;Theobald et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The predicted maximum principal strain under torsion was located at the narrowest cross-sectional area of the diaphysis, namely the mid-shaft. This is in agreement with previous experimental studies of long bones under pure torsional loads (Kress et al 1995;Theobald et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In another laboratory study, using 7-day old calf metacarpal bones, the authors show that an increase in the rate of twist generates a corresponding decrease in normalized fracture angle (inverse of fracture ratio). 7 Furthermore, some material properties of bone, such as the tensile strength and modulus, have been shown to positively correlate with age using both animal models 8 and human bones. 9 This may then influence the pattern of torsional fracture, as a spiral fracture occurs from the combination of tensile and longitudinal shear failure of long bones.…”
Section: Introductionmentioning
confidence: 99%
“…A hypothesis of the study was that the fracture ratio would increase with age, partly because tensile strength of bone has been shown to increase with age in humans 12 and animal models. 8 Secondarily, it was also hypothesized that fracture ratio would increase with the rate of twist, based on the previous study of Theobald et al 7…”
Section: Introductionmentioning
confidence: 99%
“…Each bone was tested in torsion to failure, at a rotational rate equal to 90 °/s. This rate was adopted from a previous study, in view of the absence of literature quantifying the rotational rate experienced during equivalent, ‘real-life’ fracture scenarios [ 15 ]. Previous biomechanical studies have shown that testing in torsion is the most valid method for assessing the energy absorbed to failure [ 16 ].…”
Section: Methodsmentioning
confidence: 99%